Efektivitas Penatalaksanaan Euhidrasi Terhadap Status Hidrasi Atlet Futsal - Arimbi Arimbi; Wahyana Mujari Wahid; Poppy Elisano Arfanda; Arifuddin Usman; Sarifin G (Departement of Mathematics Education, 2024)
Dehydration occurs when a person experiences a lack of fluids, or when more fluids are lost than are taken in. The effects of dehydration can vary depending on the level, from fatigue, decreased muscle strength and endurance, to decreased overall performance, and can even lead to death. This study aims to analyze the effectiveness of the euhydration strategy developed by the American Dietic Association on the hydration status of futsal athletes. This study used an experimental method with a one group pretest-posttest design. The population in this study were 20 Sport Science futsal athletes. The sampling technique used the Total Sampling technique where all populations would be samples. Hydration status was obtained by taking urine samples. Urine samples were collected from athletes before and after the match simulation using a special transparent urine container. The color of the urine was then compared with the PURI (Self Urine Check) urine color index/graph. Dehydration if the urine color scale is on a scale of 4-8 and not dehydrated/hydrated/euhydrated if the urine color scale is on a scale of 1-3. While the treatment was in the form of a euhydration strategy developed by the American Dietic Association. The results of the study showed a significant effect of the application of euhydration strategy on the hydration status of futsal athletes, with a p value = 0.000 (p <0.05). Of the 20 research samples, there were 2 respondents who had euhydration status both before and after the implementation of the euhydration protocol and no respondents (zero) who experienced dehydration before the implementation of the euhydration protocol but remained dehydrated after the implementation of the euhydration protocol. then 15 respondents who had dehydration status before the implementation of euhydration but after the implementation of the euhydration protocol had euhydration status and there were 3 respondents who remained dehydrated both before and after the implementation of the euhydration protocol.